2015
DOI: 10.5006/1686
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer of Diluted Volatile and Nonvolatile Components to a Nucleate Boiling Electrode

Abstract: The mass transfer behavior of electro-active species from bulk solution to a metal surface (Alloy 800) under subcooled boiling and fully developed nucleate boiling conditions was investigated using a novel pool-boiling device. The electrochemical method was used to measure the mass transfer rate on a boiling surface. Potassium ferricyanide and hydrogen peroxide were used as the nonvolatile and volatile reaction species, respectively. It was found that for both volatile and nonvolatile species, the mass transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, the effect of nucleate boiling bubble on the surface of SG tubing material is rarely reported because most of the high-temperature studies took place in autoclaves and the flow boiling experimental condition was difficult to maintain in autoclaves [29,30]. In the previous work [31], the effect of boiling bubble on the mass transfer behaviour was investigated; it was found that the mass transfer rate, which directly affects the cathodic corrosion reaction rate, is increased on the boiling surface in relatively low heat flux. In this study, we investigate the effects of boiling bubbles on passivity degradation on a nucleate boiling Alloy 800 surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of nucleate boiling bubble on the surface of SG tubing material is rarely reported because most of the high-temperature studies took place in autoclaves and the flow boiling experimental condition was difficult to maintain in autoclaves [29,30]. In the previous work [31], the effect of boiling bubble on the mass transfer behaviour was investigated; it was found that the mass transfer rate, which directly affects the cathodic corrosion reaction rate, is increased on the boiling surface in relatively low heat flux. In this study, we investigate the effects of boiling bubbles on passivity degradation on a nucleate boiling Alloy 800 surface.…”
Section: Introductionmentioning
confidence: 99%
“…The flow boiling system employed a similar oil heating method for follow up investigations based on our previous work. 26 The experimental set up enable us to study the effect of forced convection on mas transfer coefficient due to the micro-mixing and macro-mixing effects caused by the generation and movement of bubbles, which has never studied before. The mass transfer coefficients are determined experimentally at elevated temperatures and pressures as well as various electrolyte flow rates under a single-phase condition to verify the experimental setup.…”
mentioning
confidence: 99%